Near-Fault Ground Motion Impacts on High-Speed Rail Large-Span Continuous Girder Bridge considering Pile-Soil Interaction - Yefei Zhou; Gang Wang; Shuyi Yang; Niu Liu (Advances in Civil Engineering)
This paper examines and discusses the dynamic response of a high-speed train-bridge-soil-pile foundation system to near-fault earthquakes. A 72 + 120 + 72 m continuous girder bridge of a high-speed railroad was selected as the model for calculation. Based on the p-y model for simulating pile-soil interaction, the moment-curvature analysis program XTRACT is used to calculate the moment and curvature of bridge piers and pile foundation sections, and the finite element (FE) software is used to establish two nonlinear global bridge models under seismic effects in the high-intensity zone, one considering pile-soil interaction and one without considering pile-soil interaction. The Ap/Vp parameter, the ratio of peak acceleration to peak velocity of transverse ground shaking, is used to reflect the impulse characteristics of earthquakes and the effect of the Ap/Vp parameter on the dynamic response of bridges to earthquakes was studied. The elastic-plastic response of the bridge system was calculated under lateral and vertical near-fault (NF) impulse/NF nonimpulse/far-field (FF) ground motions (GMs). The study shows that the structural displacement increases, and the internal force decreases after considering the pile-soil interaction. The results show that the bridge piers enter the elastoplastic phase under rare earthquakes. The NF ground shaking couples with the bridge into the elastoplastic phase with a more significant impulse period than the FF ground shaking intensifies the dynamic response of the bridge structure.